Mentalexo approach for diagnosis of psychiatric disorders - TOPUZOĞLU, AHMET; ILGIN, CAN (CHURCHILL LIVINGSTONE, 2020)
Introduction: Psychiatric disorders cause a high burden of disease and disability for the society. Liquid biopsies provide potent opportunities for screening programs, diagnosis, prognostic stratification and treatment monitorization. Previously, the liquid biopsy studies were mainly focused on the several malignancies without proper screen methods, but this approach has also a strong potential for decreasing disease burden in CNS pathologies. The main restriction for the diagnosis of CNS diseases is the lack of the methods to receive biochemical/functional information form a tightly enveloped compartment. The hypothesis/theory: In this proposal, we aim to develop a fast and cheap diagnostic platform based on the detection of exosomes originating from the central nervous system (CNS) cells. We intended to develop a sensor device with minimum maintenance costs, which is highly specific and sensitive for psychiatric diseases. Evaluation of the hypothesis/idea: In order to give background information for our proposal; we began with reviewing the concept of liquid biopsies and adaptation of this concept for psychiatric disorders. Then we discussed the conventional and novel methods for the detection of extracellular vesicles (EV). Furthermore, we discussed the detection of exosomes originating from central nervous system and methods analyzing the content of the EVs. Additionally, we reviewed the imaging techniques for detection and visualization of EVs. Empirical data: We used in silico research tools (MetaCore (TM) version 6.37, Clarivate Analytics, and ExoCarta database) to detect appropriate disease specific exosomal markers. We proposed our design for the detection of EVs based on the immune-capture of EVs and detection of surface antigens via the antibody conjugated fluorophores. We also proposed a design to increase the channels for detection of exosomal antigens by using bioinformatics methods, including pathway networks, RDOC matrices and exosome databases which we called Mentalexo approach. We applied this approach on depression and addiction disorders in order to find appropriate exosomal markers. Consequences of the hypothesis and discussion: We believe that our proposal may contribute to the conception of new diagnostic devices focusing on the detection of exosomes in psychiatric conditions.
Keywords: Extracellular vesicles; Depression; Substance-related disorders; PROTEOMIC ANALYSIS; LIQUID BIOPSY; EXOSOMES; VESICLES; CANCER; MICROFLUIDICS; MEMBRANES; RDOC